Photothermal effects of gold nanorods in aqueous solution and gel media: Influence of particle size and excitation wavelength - Zendesha S. Mbalaha; David J. S. Birch; Yu Chen (IET Nanobiotechnology)
Abstract Gold nanorods (GNRs) have emerged as the most efficient photothermal agent in cancer therapy and photocatalysis. Understanding the influence of the surrounding medium, particle size, and excitation wavelength is critical to optimising the photothermal conversion rate. Here, three pairs of large and small gold nanorods of different aspect ratios and their heat generation under laser radiation at on and off surface plasmon resonance wavelengths in aqueous solution and gel‐like media are investigated. In the aqueous solution, the temperature rise of the large gold nanorods is more than with small gold nanorods at resonance excitation. In contrast to the large gold nanorods (LGNRs), the small gold nanorods (SGNRs) were less sensitive to excitation wavelength. At off‐resonance excitation, the temperature rise of the SGNRs is larger than that of the LGNRs. In the agarose gel, the photothermal effect of the SGNRs is greater than LGNRs excited at the wavelength near their solution phase longitudinal surface plasmon resonance wavelength. The temperature increase of LGNRs in gel is significantly less than in aqueous solution. These findings suggest that SGNRs could be more beneficial than the LGNRs for photothermal applications in biological systems and provides further insight when selecting GNRs.